(untitled) (World Economics and Finance Bulletin, 2022)
The article discusses the features of recognition in the accounting of fixed assets based on international financial reporting standards, reveals the significance and role of the topic under study at the present time in the development of an economic entity and ensuring the competitiveness of products. This article will consider the issue of recognition of fixed assets as one of the most important areas of accounting under IFRS based on a comparative analysis of national accounting Standards (NAS).